PENGARUH SISTEM LAMPU LED DAN REFLEKTOR DENGAN MENGGUNAKAN METODE DEEP FLOW TECHNIQUE PADA TANAMAN KALE (Brassica Oleracea Var. Sabellica) - Afrilia, Lena; Tarigan, Dafni Mawar; Anuar, Khairul; Mohamad, Munirah (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Kale (Brassica oleracea var. sabellica) is a high-value vegetable that requires adequate lighting to support photosynthesis, especially when cultivated using a hydroponic system. This study aimed to examine the effect of LED lighting and reflector use on kale growth using the Deep Flow Technique (DFT). The research was conducted in September 2024 at the Horticultural Research Center, MARDI Serdang, Malaysia, using a Completely Randomized Design (CRD) with three treatments: 4 lamps (4L), 4 lamps with reflector (4 LMR), and 5 lamps (5L), each repeated five times for a total of 1,000 plants. Observed parameters included plant height, number of leaves, chlorophyll content, and Leaf Area Index (LAI). The results showed that the 4 LMR treatment produced the best growth, with the highest number of leaves, the highest chlorophyll content, and good LAI values. The use of reflectors effectively increased light absorption efficiency and photosynthesis. In contrast, the 4L treatment showed the lowest growth due to poor lighting and nutrient deficiencies. Overall, the MARDI reflector proved effective in enhancing kale growth in a DFT hydroponic system.